19=2(b+20)-(-17)

Simple and best practice solution for 19=2(b+20)-(-17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19=2(b+20)-(-17) equation:


Simplifying
19 = 2(b + 20) + -1(-17)

Reorder the terms:
19 = 2(20 + b) + -1(-17)
19 = (20 * 2 + b * 2) + -1(-17)
19 = (40 + 2b) + -1(-17)

Multiply -1 * -17
19 = 40 + 2b + 17

Reorder the terms:
19 = 40 + 17 + 2b

Combine like terms: 40 + 17 = 57
19 = 57 + 2b

Solving
19 = 57 + 2b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-2b' to each side of the equation.
19 + -2b = 57 + 2b + -2b

Combine like terms: 2b + -2b = 0
19 + -2b = 57 + 0
19 + -2b = 57

Add '-19' to each side of the equation.
19 + -19 + -2b = 57 + -19

Combine like terms: 19 + -19 = 0
0 + -2b = 57 + -19
-2b = 57 + -19

Combine like terms: 57 + -19 = 38
-2b = 38

Divide each side by '-2'.
b = -19

Simplifying
b = -19

See similar equations:

| 1.7=0.22 | | (7*35)+(x*.14)=(7*70)+(x*.07) | | 107-11b=-1b+37 | | y-4/-3=9 | | -32(11x)+27(14x)=0+-296 | | 0=16+4x+x^2 | | =(9x)+(3x-5) | | 12=7-3x | | 3d+2d= | | 2(1+6x)+2(3-6x)=7x-3x | | (9x)+(3x-5)= | | 50+60x=-84+210x | | 35+(x*.14)=70+(x*.07) | | 35+2b=5b+11 | | 50000d=238900 | | G(x)=3-x | | x=2+0.2t | | 99-14b=-5b+63 | | 0.2*0.02= | | (3x-1)+2(2x+6)=5x-3 | | 3b+4b-2=26 | | 0.25x+0.5x=1.5 | | 3(2v+1)-5= | | sqrt(2x)-(1)/(sqrt(2))=sqrt(8x) | | 9(u-2)=-4u-44 | | 9+27r=8-12r | | 4u+30=6(u+4) | | .85x+0.05(14-x)=.10(-41) | | 99-115=-4(-4y)-9(2y)+y | | 5(v-4)=5v+20 | | -16+15= | | 2q+379=833 |

Equations solver categories